A Model of the Molecular Aggregate Processes of Hemoglobin S. Absence of Cristallization (2008)
The molecular aggregate formation mechanisms play a major role in the interpretation of the pathophysiology of Sickle Cell disease and in the selection of the therapeutic strategies to follow.  A mechanism and a mathematical model are proposed. The model postu-lates the existence of defective microtubules formed by deoxy hemoglobin S and oxy hemoglobin S, and explains the dependence of polymerization on hemoglobin concentration, temperature, and partial oxygen pressure. The analysis focuses on the polymerization of hemoglobin S in the absence of crystallization. The action of other kinds of hemoglobin in the molecular aggregate formation process can be explained.